Suara Kupu-Kupu Malam dalam Novel Kelir Slindet Karya Kedung Darma Romansha: Kajian Feminisme - Wahyuni, Sri (Jurnal Bahasa dan Sastra, 2024)
The purpose of this study is to reveal the voices of night butterfly in the novel Kelir Slindet by Kedung Darma Romansha. Women are exotic figures who never run out of charm to talk about, especially prostitutes. In the analysis, the researcher uses the theory of feminism as a knife of analysis for the voice of prostitutes. This study uses a qualitative descriptive method with the novel Kelir Slindet as the object of study. The data collection method used literature study with analytical descriptive technique as a data analysis technique. The research findings show that the voices of night butterfly include: (i) complaining about being the backbone of the family; (ii) have high hopes for their children; (iii) wants his son to marry the son of a pilgrim; (iv) insisting on their child’s future to be happy; (v) does not accept when his child is seen as equal to him; (vi) ordered that their children marry a responsible man; and (vii) always hope and ask for the happiness of his child. With the presence of the novel Kelir Slindet, the author wants to open his eyes and change the paradigm of society about women who are prostitutes. This shows one of the functions of literature as a tool for teaching moral values. Life messages and teachings do not always come from good things but even bad things.